AN ANALYSIS OF THE MEANING OF THE SHI‘R ṢALAWĀT SIMṬ AL-DURAR BY ḤABĪB ‘ALĪ IBN MUḤAMMAD AL-ḤABSHĪ IN THE SEMIOTIC STUDY OF RIFFATERE - Muhammad Fajar Tubagus Dewantara; Kamal Yusuf; Sodikin Sodikin (CMES (Center of Middle Eastern Studies), 2025)
Ṣalāwat is a religious form of expression in the Islamic world that serves as a form of prayer and praising the prophet Muhammad and a tool of preaching and cultural identification. One of the most influential texts of the Ṣalāwat Simṭ al-Durar of Habib Ali bin Muhammad Al-Habsyi, but the symbolic expressions contained are usually not fully interpreted. The paper uses qualitative textual analysis to apply the Riffatere semiotic theory developed by Michael Riffaterre which is based on the idea of indirect expression by displacement, distortion and meaning creation. The Simṭ al-Durar manuscript was used as primary sources with the support of the sharḥ literature, scholarly research, and interviews with religious leaders. The symbols that are identified in the analysis include light (nūr), which means prophetic guidance, pearls and jewels, which is a symbol of spiritual purity, fragrance, which is a blessing of God, and journey, which is the spiritual development of the believer. These symbols are multilayered theological and devotional meanings not to be interpreted literally. The results indicate that Simṭ al-Durar is an enriched semiotic text that reinforces religious tradition and gives communal spiritual awareness.